PERSUASIVE STRATEGIES OF SAMOSIR PROMOTION IN “Visit Samosir” FACEBOOK PAGE - Renni Sagala; Yeni Erlita (State University of Medan, 2017)
This study deals with the Persuasive strategies of Samosir promotion in visit samosir facebook page. The objective of the study are to find out the types of persuasive technique of samosir promotion in visit samosir facebook page, and to describe the strategies of persuasive of samosir promotion in visit samosir facebook page. This study was conducted by using Descriptive qualitative method. The data was collected from http://visitsamosir.com. There were 60 status from May of 2016 to May of 2017.The findings found that there are only six from seven types of persuasive technique are used in visit samosir status and they are rationalization (17 status), identification (3 status), suggestion (32 status), compensation (6 status), projection (2 status), and displacement (1 status). And the strategy of persuasive that used in visit samosir facebook page were Logos, Phatos, Ethos. Mostly, the user use the logical reason (Logos). It caused the user need to show the fact or logic reason to get belief from the visitor. So, the visitor become interest to visit the tourism